Design And Development Of A Tracer Study Information System For SMKN 2 Garut Based On Website Using Prototype Method - Hidayat, Ramdhani; Rahayu, Dinar; Faraz Mutaqin, Ahmad (RISTEC : Research in Information Systems and Technology, 2023)
In the current era, technological advancements in Indonesia have created extensive resources for information and communication for the community also equal with basic human needs such as clothing and food. SMKN 2 GARUT is a favorite school in Garut city, with a focus on academic and non-academic achievements. Despite the school utilizing technology such as a website, the alumni data management system, including tracer studies, is still conducted manually. This research for develop a website-based tracer study information system for SMKN 2 GARUT. Currently, alumni data is collected through the filling of biodata forms, which are then submitted to the Counseling guidance for consolidation and management. After verification, the data is sent to Headmaster. However, the system still relies on manual processes with the use of poorly managed gform links. This leads to delays in information delivery, ease of data duplication, and human error risks. In this research, the researcher employs the prototype development method, which includes requirement analysis, prototype design, system implementation, program coding, and testing. The tracer study system is developed using PHP 7.0 programming language with CodeIgniter framework and MySQL database. Based on the conducted development analysis, this application improves the average time efficiency compared to the previous system. Additionally, the use of this application reduces costs in generating alumni data reports and facilitates alumni data management at SMKN 2 GARUT. This tracer study information system effectively manages alumni data, provides appropriate control, and can be accessed through internet technology.